An Assessment of Disaster Loss and Damage in Nepal (The Geographic Base, 2019)
A disaster is a natural or manmade hazard resulting in an event of substantial extent causing significant physical damage or destruction, loss of life or drastic change to the environment. Due to diverse geographical coverage, Nepal is prone to various geological and hydro-meteorological hazards. This paper tries to show the types of disaster, losses and damages induced by disaster and analyze the trend and geographical distribution of disaster in Nepal. This study is based on the secondary data sources. Disaste r events data were collected from NSET and other government research papers, library etc. 26,665 events were reported during a 45 year and 43,868 people were died, 2,828 people were missing by disaster. Fire, flood landslide, accident and thunderstorms are major disasters in terms of occurrences and Earthquake, flood, and landslide are the major disasters in terms of damages and losses. The trend of disaster events is gradually increasing from the 1971 to 2000 but after 2000 the trend of disaster is drastically increasing to 2016. Annually 593 disaster events have occurred in Nepal. The data of impacts caused by the disasters also reveal that the estimated annual economic loss is increasing with the increasing frequency of disasters. The number of natural disasters as well as the number of corresponding casualties, injured and affected people, and economic loss is steadily on the rise. Tarai and Hilly districts are highly vulnerable than Mountain districts and Hill and Tarai region are most affected than Mountain region due different disaster in Nepal. The Tarai and some central hill districts are most vulnerable in terms of disasters occurrences. Among the seven provinces, province no 3 recorded the highest number of human deaths and disasters occurrences.